Analisis Stabilitas Lereng Menggunakan Model Numerik 3 Dimensi Studi Kasus Lereng Sekolah Terpadu di Kecamatan Jonggol Bogor - desti santi pratiwi; Nirpan Lesmana; Indra Noer Hamdhan (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2020)
Slope is the surface of the earth that forms an inclination angle, that it has the potential for landslides. Landslide will be occurred by several factors, such as steep slopes, large loads, high rain intensity, poor drainage systems, high ground water levels and others. Therefore, slope stability analysis is needed to ensured that the slopes are safe from landslides potential which injured many people. As for the prevention and handling of landslides that can be done, such as changing the geometry of the slopes, improving the drainage system, providing slope reinforcement such as gabions, retaining walls, poles and others. This study aims to determine the effect of water level on the stability of the existing slope and which has been reinforced by bored piles using a 3-dimensional numerical model. The case study reviewed is the slope in the Integrated School in Bendungan Village, Jonggol District, Bogor Regency. The results of the analysis show that in the existing conditions with a normal water level, the value of the safety factor (SF) is 1.16, and when the water level is critical, the SF value is 1.14. Whereas in slope conditions with the reinforcement of the bored pile, the analysis results show that the SF value with normal water level is 2.33 and when the water level is critical is 1.58. The results of the analysis with the reinforcement of the drill pile show that the SF value is more than 1.5 so that the slope is safe from landslide based on SNI 8460 of 2017.